Efficacy and Safety of Infliximab in HLA-B27-associated Ocular Inflammation Refractory or Intolerant to Conventional Immunomodulatory Therapy - Bajwa, Asima; Maleki, Arash; Payal, Abhishek R; Fandiño, Adriana; Padrón, María Inés Menéndez; Walsh, Marisa; Foster, Charles Stephen (Journal of Ophthalmic and Vision Research, 2020)
Purpose: To determine the efficacy and safety of infliximab therapy in patients with HLA B-27-associated ocular inflammation resistant or intolerant to conventional immunomodulatory therapy. Methods: This was a retrospective observational case series. All cases were uveitic patients with positive HLA-B27, confirmed through HLA testing, resistant or intolerant to conventional immunomodulatory therapy. The primary outcome of the study was to identify the efficacy of infliximab determined by the control of inflammation, duration of remission, and the ability to reduce conventional immunomodulatory therapy. The secondary outcome was an improvement of two or more lines of best-corrected visual acuity (BCVA) on the Snellen visual acuity chart. Results: Twenty-four patients (38 eyes) were included in the study. All patients were followed for 24 months. Twenty-one (87.5%) patients completed 24 months of follow-up. Sixteen (66.7%) patients had active uveitis at the beginning of therapy. One patient out of these active patients had active inflammation at the end of follow-up period. Thirteen (87.5%) out of sixteen active patients were in steroid-free remission. The mean duration of treatment to induce remission was 16.5 months (range 6–24 months). Corticosteroid was stopped in 19 (90.5%) patients by the end of the study. At the end of the study, in patients who achieved remission, 14 (58.3%) patients were in remission on infliximab therapy and 6 (25%) patients were in remission off infliximab therapy. Of the 38 eyes, 8 (21.05%) showed improvement in BCVA (three eyes had successful cataract extraction with intraocular lens implantation during infliximab therapy with no subsequent inflammation), while 26 eyes (68.4%) had stable BCVA over the 24-month study period. The side effects included allergic reaction, fatigue, cellulitis, headache, restlessness, elevation of liver enzymes, and anemia. Two patients (n = 24, 8.3%) experienced severe adverse effects and the treatment was stopped prematurely in these two patients. Conclusion: Infliximab might induce and maintain the steroid-free remission in HLAB27- associated ocular inflammation in patients resistant or intolerant to conventional immunomodulatory therapy.